If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 25y * 2n = n + y Reorder the terms for easier multiplication: 25 * 2y * n = n + y Multiply 25 * 2 50y * n = n + y Multiply y * n 50ny = n + y Solving 50ny = n + y Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-1n' to each side of the equation. -1n + 50ny = n + -1n + y Combine like terms: n + -1n = 0 -1n + 50ny = 0 + y -1n + 50ny = y Combine like terms: y + -1y = 0 -1n + 50ny + -1y = 0 The solution to this equation could not be determined.
| 85=x+-8 | | 6x/(x-1)=3 | | 54-8x=20 | | 5x-9=3(5x+3) | | 6x/(x-1)3 | | 4a+5-7a= | | -11/2/4 | | 9x^2-(7x-2)(x+3)=-12x+1 | | 8x^3+45= | | X=120+5x | | -4x-11y-9x+15y= | | x^4-2x^2+6x=0 | | 8x^3+45=2x(2x+21) | | y=2(x+3)(x+3)-32 | | y=8ln(3x-2)-4 | | y=2(x+3)-32 | | Y=2x^2-11x+18 | | Y=3.75(5) | | 10x=(50*2) | | 6h-10=6h+10 | | 11=f-4 | | 7.4r+9+2r=18 | | 2x+6=-2(-x-3) | | 2=4x+3(-3x) | | 4(w-2)=4w+2-3(-2w-2) | | .5(8x+6)+.1111111111(63x+45)= | | 6(3+3m)=-4m+8(4m-4) | | ln(x)-x=ln(y/2) | | 3a+2b=15 | | 2n-32=8(n-7) | | 11n-12-10n-1=-11 | | 2-4+=0 |